Synthesis and Potentiometric Sensor Applications of a Hydrazone Derivative Molecule: Fast and Selective Determination of Cobalt(II) Ions - Ozbek, Oguz; Kalay, Erbay; Cetin, Alper; Isildak, Omer; Tokali, Feyzi Sinan; Aslan, Osman Nuri; Isildak, Ibrahim (WILEY-V C H VERLAG GMBH, 2022)
In this study, a simple and highly selective potentiometric sensor has been developed for the determination of cobalt(II) ions based on a poly(vinly chloride) (PVC) membrane. As an ionophore, a hydrazone derivative molecule (3) was synthesized for the first time, and its characterization was completed using NMR, FT-IR and Q-TOF spectroscopic techniques. The developed sensor works well in the linear concentration range of 1.0x10(-6)-1.0x10(-1) M with Nernstian slope of 28.6 +/- 1.7 mV/decade of activity. The developed cobalt(II)-selective sensor has a low detection limit of 3.09x10(-7) M, and a very fast response time of 5 seconds. The sensor, which exhibits a highly selective behaviour towards cobalt(II) ions compared to other metal cations, works in the pH range of 6.0-10.0 without being affected by changes in pH. The developed sensor could be used as an indicator electrode in potentiometric titration of Co(II) ions with EDTA. Finally, the developed cobalt(II)-selective sensor was successfully used for the determination of Co(II) in various water samples.
Keywords: Cobalt(II); Hydrazone derivatives; Potentiometry; Sensors; Synthesis; ELECTRODE; EXTRACTION; COMPLEXES; CHLORINE; WATER; Chemistry